GATA1 downregulation in prefibrotic and fibrotic stages of primary myelofibrosis and in the myelofibrotic progression of other myeloproliferative neoplasms. (January 2021) - Sangiorgio, Valentina Fabiola Ilenia; Nam, Anna; Chen, Zhengming; Orazi, Attilio; Tam, Wayne
Highlights: In primary myelofibrosis, GATA1 is downregulated early at the pre fibrotic stage. pre-PMF shows reduced GATA1 expression compared to ET. In PV and ET GATA1 decreases during the fibrotic progression. GATA1 reduction in the fibrotic progression affects mostly the full length isoform. Abstract: GATA binding protein 1 (GATA1) is a transcription factor essential for effective erythropoiesis and megakaryopoiesis. Two isoforms of GATA1 exist, derived from alternative splicing. "GATA1" is the full length and functionally active protein; "GATA1s" is the truncated isoform devoid of the activation domain, the function of which has not been fully elucidated. Reduced megakaryocytic expression of GATA1 has been linked to impaired hematopoiesis and bone marrow fibrosis in murine models and in vivo in patients affected by primary myelofibrosis (PMF). However, data is limited regarding GATA1 expression in other myeloproliferative neoplasms (MPN) such as pre-fibrotic PMF (pre-PMF), polycythemia vera (PV) and essential thrombocythemia (ET) and in their respective fibrotic progression. To assess whether an immunohistologic approach can be of help in separating different MPN, we have performed a comprehensive immunohistochemical evaluation of GATA1 expression in megakaryocytes within a cohort of BCR-ABL1 negative MPN. In order to highlight any potential differences between the two isoforms we tested two clones, one staining the sum of GATA1 and GATA1s ("clone 1"), the other staining GATA1 full length alone ("clone 2"). At the chronic phase, a significant reduction preferentially of GATA1 full length was seen in pre-fibrotic PMF, particularly compared to ET and PV; no significant differences were observed between PV and ET. The fibrotic progression of both PV and ET was associated with a significant reduction in GATA1, particularly affecting the GATA1 full length isoform. The fibrotic progression of pre-PMF to PMF was associated with a significant reduction of the overall GATA1 protein and a trend in reduction of GATA1s. Our findings support a role of GATA1 in the pathogenesis of BCR-ABL1 negative MPN, particularly in their fibrotic progression and suggest that the immunohistochemical evaluation of GATA1 may be of use in the differential diagnosis of these neoplasms.